Morphology, mineralogy and magnetic susceptibility of epikarst-Terra Rossa developed in late Quaternary aeolianite deposits of southeastern Saurashtra, India - Khadkikar, Aniruddha S.; Basavaiah, N. (My University, 2004)
The nature and development of epikarst and soil development in aeolianites under a monsoonal climatic regime has not yet been described. Late Quaternary aeolianites of the southeastern coast of Saurashtra in western India show a wide array of epikarst and red-soil formation, and serve to typify the character of aeolianite weathering under a monsoonal climate. Three varieties of epikarst are identified that represent down-profile increase in groundwater flow. Five types of Terra Rossae represent a transition from the karstified limestone to soil development. Terra Rossae differ in the content of residual aeolianite and show both simple and complex profiles. The latter at places shows ped development. The results show that an ontogenetic (growth) sequence exists from incipient epikarst to complex palaeosols. This ontogenetic sequence represents an incremental increase in the groundwater budget of the region in response to changing intensification of the Indian monsoon rainfall. Magnetic properties of the Terra Rossae formed under a monsoonal climate are described for the first time. The magnetic susceptibility together with its frequency-dependent and anhysteretic remanent magnetization (ARM) represents both the concentration of single domain and ultrafine superparamagnetic (SP) magnetite. The formation of single domain and superparamagnetic magnetite and hematite are linked genetically to weathering of the aeolianite that leads to the formation of Terra Rossa.
Keywords: Epikarst; Terra Rossa; Monsoon; Aeolianite; Carbonate; Diagenesis; Magnetic susceptibility; Mineralogy; India